Adenosquamous carcinoma of the oral cavity: An unusual epithelial malignancy. A report of two cases and review of literature. Issue 1 (January 2015) - Bhattacharyya, Indraneel; Chehal, Hardeep K.; McNally, Stuart J.; Cohen, Donald M.; Islam, Nadim M.
Abstract Adenosquamous carcinoma (ASC) is a rare and somewhat controversial variant of squamous cell carcinoma. The WHO classification of tumors of the head and neck in 2005 defined this entity as "a malignant tumor with histological features of both adenocarcinoma and squamous cell carcinoma." ASC is associated with an aggressive behavior and poor prognosis. A thorough search of the literature yielded 35 oral cases predominantly affecting middle aged to elderly males. We aim to add two cases of ASC arising in the oral mucosa. Both cases demonstrated the glandular malignant neoplasm in the deeper aspects of the specimen and squamous carcinoma toward the superficial aspects. Both patients were treated with combined surgery and/or chemoradiotherapy; however, one of the patients died of disease after multiple recurrences. In addition, we review and discuss the published cases of ASC in the literature with special emphasis on the diagnosis, treatment and prognostic pattern. It is imperative that ASC be distinguished from routine adenocarcinomas and squamous cell carcinomas including the variants due to its recurrence potential and poorer outcome. Further reporting and longitudinal studies may be beneficial in understanding this disease and its long term impact in improving patient morbidity and mortality.